ESTIMASI JARAK GENETIK DAN FAKTOR PEUBAH PEMBEDA BANGSA BABI (Berkshire, Duroc, Landrace dan Yorkshire) MELALUI ANALISIS MORFOMETRIK DI BPTU BABI DAN KERBAU SIBORONGBORONG - netro banjarnahor (Universitas Sumatera Utara, 2014)
ABSTRACT NETRO BANJARNAHOR, 2014 : Genetic Distance Estimation and Variable Differential Factor of pig breeds (Berkshire, Duroc, Landrace and Yorkshire) through Morphometrics analysis in BPTU Pig and Buffalo Siborongborong. Under supervisied by USMAN BUDI and HAMDAN. Genetic distances provide little opportunity to obtain heterosis in crosses. Therefore the genetic distance be a guide in conducting cross. The object of the research to identify factors differentiating variables and estimate the genetic distance between the pig breeds (Berkshire, Duroc, Landrace and Yorkshire). This research was conducted in the Superior Livestock Breeding Center, (BPTU) Pig and Buffalo Siborongborong using Berkshire (17 pigs), Duroc (22 pigs), Landrace (46 pigs) and Yorkshire (25 pigs). Data collection was done by measuring the observed variables are shoulder height, hip height, hip width, body length, chest girth, inchest, tail length, neck circumference, head length, head width, ear length and ear width. The data obtained were processed using a simple discriminant analysis using the SAS program (Statistical Analysis System) and Dendogram using the program MEGA (Molecular Evolutionary Genetic Analysis). The results showed that the phenotypically purity of Berkshire pigs (88.24%), Duroc pigs (86.36%), Landrace pigs (89.13%) and Yorkshire pigs (68.00%). Variable differential factor for body morphometrics was ear width, ear length, head width, head length and tail length. Berkshire and Yorkshire has a close genetic distance, while the Duroc and Landrace has a far genetic distance. Keywords : pig , morphometrics , genetic distance, phenotypically purity